2018
DOI: 10.1021/acs.analchem.7b04590
|View full text |Cite|
|
Sign up to set email alerts
|

Liquid Chromatography-High Resolution Mass Spectrometry Analysis of Platelet Frataxin as a Protein Biomarker for the Rare Disease Friedreich’s Ataxia

Abstract: Friedreich's ataxia (FA) is an autosomal recessive disease caused by an intronic GAA triplet expansion in the FXN gene, leading to reduced expression of the mitochondrial protein frataxin. FA is estimated to affect 1 in 50 000 with a mean age of death in the fourth decade of life. There are no approved treatments for FA, although experimental approaches, which involve up-regulation or replacement of frataxin protein, are being tested. Frataxin is undetectable in serum or plasma, and whole blood cannot be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 47 publications
3
70
0
Order By: Relevance
“…PBMC and platelet frataxin expression has previously been used as an FRDA biomarker (49,50): these cells are easily accessible and have GLP-1 receptor expression levels comparable to iPSC-neurons (Supplemental Figure 6A). Because frataxin protein is challenging to quantify (51), frataxin was measured using 3 methods, namely Western blot, lateral flow dipstick immunoassay, and ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…PBMC and platelet frataxin expression has previously been used as an FRDA biomarker (49,50): these cells are easily accessible and have GLP-1 receptor expression levels comparable to iPSC-neurons (Supplemental Figure 6A). Because frataxin protein is challenging to quantify (51), frataxin was measured using 3 methods, namely Western blot, lateral flow dipstick immunoassay, and ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…Buccal cell frataxin levels correlate with disease severity, but they are present in very low levels, and their changes may not match neurological function . Whole blood frataxin levels largely represent levels in erythrocytes, where frataxin has a slightly different amino acid sequence and is made from a different splice variant . These levels are unlikely to correlate with neurological function.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, some of the difficulties in frataxin measurement could be resolved using novel frataxin assays based on mass spectrometry, which markedly improves reproducibility (Fig. ; ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it will be important in the future to assess frataxin levels in particular FA cases in order to determine whether there is a threshold level required for optimal ApoA-I secretion. We have recently developed an assay to rigorously quantify mature frataxin in human platelets as surrogates for liver tissue so that such determinations can be readily made [ 48 ]. Interestingly, there were four FA patients with serum ApoA-I levels that were in the normal range and repeat analyses confirmed that this was not due to assay specificity.…”
Section: Discussionmentioning
confidence: 99%